Population genomics uncovers loci for trait improvement in the indigenous African cereal tef (Eragrostis tef) - Jones, M.R.W.; Kebede, W.; Teshome, Abel; Girija, A.; Teshome, A.; Girma, D.; Brown, J.K.M.; Quiroz-Chavez, J.; Jones, Christopher S.; Wulff, B.B.H.; Assefa, K.; Tadele, Z.; et al. (Nature Research, 2025)
Tef (Eragrostis tef) is an indigenous African cereal that is gaining global attention as a gluten-free “superfood” with high protein, mineral, and fibre contents. However, tef yields are limited by lodging and by losses during harvest owing to its small grain size (150× lighter than wheat). Breeders must also consider a strong cultural preference for white-grained over brown-grained varieties. Tef is relatively understudied with limited “omics” resources. Here, we resequence 220 tef accessions from an Ethiopian diversity collection and also perform multi-locational phenotyping for 25 agronomic and grain traits. Grain metabolome profiling reveals differential accumulation of fatty acids and flavonoids between white and brown grains. k-mer and SNP-based genome-wide association uncover important marker-trait associations, including a significant 70 kb peak for panicle morphology containing the tef orthologue of rice qSH1—a transcription factor regulating inflorescence morphology in cereals. We also observe a previously unknown relationship between grain size, colour, and fatty acids. These traits are highly associated with retrotransposon insertions in homoeologues of TRANSPARENT TESTA 2, a known regulator of grain colour. Our study provides valuable resources for tef research and breeding, facilitating the development of improved cultivars with desirable agronomic and nutritional properties.